Modeling AI readiness in a faith-based educational context: Evidence from Adventist schools in Western Indonesia using a hierarchical PLS-SEM approach - Henry Pandia; Wei Hung Chen (Institute of Information Technology and Social Science (IITSS), 2026)
This study examines the influence of AI literacy and AI ethics awareness on teachers’ readiness to adopt artificial intelligence in educational practice. As AI technologies become increasingly integrated into teaching and learning processes, understanding the factors that shape teachers’ preparedness is essential. Data were collected from 204 teachers in Adventist schools in Western Indonesia and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that AI literacy significantly predicts AI readiness (β = 0.491, p < 0.001), while AI ethics awareness shows a positive but weaker effect (β = 0.313, p < 0.001). The model explains 53.1% of the variance in AI readiness, indicating moderate to substantial explanatory power. AI readiness is conceptualized as a multidimensional construct comprising confidence, intention, and digital self-learning. These findings suggest that cognitive competence plays a more dominant role than ethical awareness in shaping readiness. This study contributes by providing empirical evidence within a faith-based educational context and by advancing the conceptualization of AI readiness as a hierarchical construct. The results highlight the importance of AI-specific professional development and ethical awareness to support responsible AI integration in education.